# For #f(t)= (t-2,-t^2-2t)# what is the distance between #f(2)# and #f(5)#?

The distance is

By signing up, you agree to our Terms of Service and Privacy Policy

To find the distance between ( f(2) ) and ( f(5) ), we first need to evaluate ( f(t) ) at ( t = 2 ) and ( t = 5 ), then calculate the distance between the resulting points.

( f(2) = (2 - 2, -(2)^2 - 2(2)) = (0, -8) )

( f(5) = (5 - 2, -(5)^2 - 2(5)) = (3, -35) )

Using the distance formula:

( d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} )

Substitute the values:

( d = \sqrt{(3 - 0)^2 + (-35 - (-8))^2} )

( d = \sqrt{3^2 + (-35 + 8)^2} )

( d = \sqrt{9 + (-27)^2} )

( d = \sqrt{9 + 729} )

( d = \sqrt{738} )

Therefore, the distance between ( f(2) ) and ( f(5) ) is ( \sqrt{738} ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- What is the arclength of #f(t) = (sqrt(t^2-2t+1),t^2-2t+1)# on #t in [0,1]#?
- How do you differentiate the following parametric equation: # x(t)=tsqrt(t^2-1), y(t)= t^2-e^(t) #?
- How do you convert parametric equation to cartesian x = t - 2 and y = -(t²) + t + 1?
- What is the derivative of #f(t) = (t^2-sint , t-1 ) #?
- What is the derivative of #f(t) = (e^t/t +e^t, e^t-cost ) #?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7